Pengaruh Karakteristik Komite Audit Dan Auditor Quality Terhadap Audit Report Lag - Angelina Siahaya; Chyntia Angelina; Juniarti Juniarti (Business Accounting Review, 2020)
The purpose of this research is to find out the impact of audit committee's characteristic from audit committee financial expertise, audit committee gender, and auditor quality on audit report lag. The independent variable in this research are audit committee financial expertise (ACexp), and audit committee gender (ACgen) that are measured by ratio scale through percentage, and auditor quality (AQ) that are measured by dummy variable. For the dependent variable, this research uses audit report lag that is measured with a day-count scale. The sample used for this research includes 185 mining companies that has been signed in Indonesia Stock Exchange (IDX) for 5 periods in 2015-2019. The collected datas are from financial reports, annual reports, and bloomberg. This research is processed by GRETL software with analytic model in form of data panel regretion and final model in form of Generalized Least Square (GLS). The result of this research stated that audit committee financial expertise, audit committee gender, and auditor quality, have a negative and significant impact on audit report lag.